An imported case of melioidosis presenting as pyelonephritis/urosepsis. Issue 5 (15th September 2015) - Monecke, Stefan; Friedrichs, Anette; Pöhlmann, Christoph; Hochauf, Kristina; Gunzer, Florian; Wiesner, Diana; Sickert, Wolfgang; Steinmetz, Ivo; Scholz, Holger; Ehricht, Ralf; Schmoock, Gernot; Jacobs, Enno
Abstract : Introduction: Melioidosis, a potentially life-threatening disease caused by Burkholderia pseudomallei, is common in Northern Australia and south-east Asia, but it is rarely encountered in the western world. However, due to increased travel, imported cases have been observed among tourists to endemic areas. The clinical manifestations are highly variable. Case presentation: We report a case of melioidosis presenting as pyelonephritis/urosepsis in a previously healthy German tourist who had travelled to several endemic regions. Conclusion: The described case highlights the fact that the diagnosis of melioidosis may be surprising to a routine diagnostic laboratory. An accidental and unwitting exposure of laboratory staff may occur before a definite identification is achieved. Good communication between the clinician and laboratory staff is crucial, especially with respect to travel histories.